Governance at source through management accounting benchmarking: A way forward for the public sector - Rahman, Ibrahim Kamal Abdul; Azhar, Zubir; Omar, Normah; Sulaiman, Suzana (International Journal of Psychosocial Rehabilitation, 2020)
Benchmarking of management accounting involves the search for best practices amongst players in the industry and is considered critically important for organisational survival as it promotes the application of best management tools and techniques to achieve superior value creation and business performance. Despite the allegations that management accounting has lost its relevance for not providing adequate support to business managers within the competitive global economy, tools and techniques such as balanced scorecard, key performance indicators and economic value added have been applied rigorously. In view of this, the National Award for Management Accounting (NAfMA) was pioneered in Malaysia which aimed towards “regaining management accounting prominence” where the award’s focuses were on the management accounting excellence, management accounting best practices and management accounting best practice solutions. In essence, management accounting can be considered as “governance at source” where management accountants provide relevant financial and non-financial information to the management teams to facilitate them to make the best decisions for their respective organisations. Moving forward, we posit that a special management accounting award for the public sector should be developed and promoted in which new elements such as leadership, management accounting information, resource management, community and customer focus, stakeholder partnership management, performance management and service delivery outcomes are embedded in the new suggested framework. This paper proposes the award criteria that propagate accountability, transparency, efficiency and effectiveness for sustainable value creation amongst the Malaysian public sector entities.